Pluralism of Pluralism: A Pluralistic Probe into Philosophizing - Kurian, Ajeesh (Journal of Dharma, 2008)
Johnson J. Puthenpurackal, ed., Pluralism of Pluralism: A Pluralistic Probe into Philosophizing, Bangalore: Asian Trading Corporation, 2006, pages: xxi + 393, ISBN: 81-7086-392-9.